Contribuição dos impactos na saúde bucal e de variáveis sociodemográficas e clínicas na qualidade de vida relacionada à saúde - Zucoloto, Miriane Lucindo [UNESP] (2014)
Objectives: Estimate the psychometric properties of the instruments Oral Health Impact Profile (OHIP) and its reduced version (OHIP-14), Multidimensional Pain Inventory (MPI) and Short Form Health Survey (SF-36) when applied to dental patients and evaluate the contribution of impacts on oral health and sociodemographic and clinical variables on health-related quality of life. Methods: A total of 1,203 adult subjects enrolled in the Faculty of Dentistry of Araraquara - UNESP from September/2012 to April/2013 participated in the study. The mean age was 43.4 (DP=14.7) years and 71.7% were female. The Sociodemographic and clinical variables collected were gender, age, socioeconomic status, presence and location of pain, preexisting chronic disease, dental condition, use of dental prosthesis and the type. The evaluation of the psychometric properties of the instruments was performed using Confirmatory Factor Analysis (CFA). 2/df, CFI, GFI, TLI, PGFI and RMSEA were used as indices of goodness-of-fit. The Convergent validity was estimated by the average variance extracted (AVE). Convergent validity was estimated by Average Variance Extracted (AVE) and Composite Reliability (CC). Internal consistency was evaluated by standardized Cronbach alpha coefficient. The stability (factorial invariance) of the models was tested in independent samples by multigrupos analysis (Δ2). To assess the contribution of the impacts on oral health, sociodemographic and clinical variables on health-related quality of life, the data were included in a structural equation model. The factor Health was the central construct. The predictive model was evaluated based on the statistical significance of the causal paths (), assessed by the z test, considering a significance level of 5%. Results: For the OHIP, we observed best-fit models of the reduced version (OHIP-14) and among users of dental prosthesis. Convergent validity was compromised in the factors...